Long-term outcome following microwave ablation of lung metastases from colorectal cancer - Han, Yue; Yan, Xue; Zhi, Weihua; Liu, Ye; Xu, Fei; Yan, Dong (Frontiers in Oncology, 2022)
Abstract Purpose: To retrospectively evaluate the safety and efficacy of percutaneous computed tomography (CT)-guided microwave ablation (MWA) in colorectal cancer (CRC) lung metastases, and to analyze prognostic factors. Materials and methods: Data were collected from 31 patients with CRC lung metastases from May 2013 to September 2017. They had removed the CRC, no extrapulmonary metastases, no more than three metastases in the lung, the maximum diameter of the lesions was ≤3 cm, and all the lung metastases could be completely ablated. The ablation procedures were performed using a KY-2000 microwave multifunctional therapeutic apparatus. Efficacy is assessed two to four weeks after ablation, and follow-up are performed every three months for two years. The primary outcome was overall survival (OS). The secondary outcomes were progression-free survival (PFS), and complications. Cox regression analysis was used for the evaluation of the statistical significance of factors affecting the end result of MWA therapy. The Kaplan–Meier method was used for estimation of survival rates. Results: A total of 45 metastatic lung lesions from CRC in 31 patients were treated with CT-guided MWA procedures. The median OS was 76 months. The one, two, three, and five-year survival rates were 93.5%, 80.6%, 61.3%, and 51.6%, respectively. Multivariate analysis showed that the primary tumor from the rectum (P = 0.009) and liver metastases at the diagnosis of lung metastases (P = 0.043) were risk factors affecting OS, while PFS was a protective factor. The median PFS was 13 months. The maximum diameter of lung metastases lesions (P = 0.004) was a risk factor. The interval between pulmonary metastases and MWA (P=0.031) was the protective factor. Pneumothorax was observed in 13 out of 36 procedures. Four patients developed pneumothorax requiring drainage tube insertion. No patient deaths occurred within 30 days of ablation. Three out of 31 patients (9.67%) were found to have local recurrence of the original lung metastatic ablation foci. Conclusion: MWA therapy may be safely and effectively used as a therapeutic tool for the treatment of selected CRC pulmonary metastases, and the prognosis is better in patients without liver metastases at the diagnosis of lung metastases.